In Vivo Incorporation of Photoproteins into GroEL Chaperonin Retaining Major Structural and Functional Properties - Victor Marchenkov; Tanya Ivashina; Natalia Marchenko; Natalya Ryabova; Olga Selivanova; Alexander Timchenko; Hiroshi Kihara; Vladimir Ksenzenko; Gennady Semisotnov (Molecules, 2023)
The incorporation of photoproteins into proteins of interest allows the study of either their localization or intermolecular interactions in the cell. Here we demonstrate the possibility of in vivo incorporating the photoprotein Aequorea victoria enhanced green fluorescent protein (EGFP) or Gaussia princeps luciferase (GLuc) into the tetradecameric quaternary structure of GroEL chaperonin and describe some physicochemical properties of the labeled chaperonin. Using size-exclusion and affinity chromatography, electrophoresis, fluorescent and electron transmission microscopy (ETM), small-angle X-ray scattering (SAXS), and bioluminescence resonance energy transfer (BRET), we show the following: (i) The GroEL14-EGFP is evenly distributed within normally divided E. coli cells, while gigantic undivided cells are characterized by the uneven distribution of the labeled GroEL14 which is mainly localized close to the cellular periplasm; (ii) EGFP and likely GLuc are located within the inner cavity of one of the two GroEL chaperonin rings and do not essentially influence the protein oligomeric structure; (iii) GroEL14 containing either EGFP or GLuc is capable of interacting with non-native proteins and the cochaperonin GroES.